Assessment of early postoperative pain and haemorrhage in young children undergoing dental extractions under general anaesthesia - PENELOPE A. McWILLIAMS, & JOHN S. RUTHERFORD (IAPD and Blackwell, 2007)
There are existing guidelines and evidence for dental clinicians on the use of general anaesthesia for treatment of children, relating to prescribing of this technique, treatment planning for such interventions.